MGM563 – Statistical Inference (Pentaabiran Statistik) - PPSM, Pusat Pengajian Sains Matematik (2022)
Second Semester Examination 2021/2022 Academic Session July 2022 MGM563 – Statistical Inference (Pentaabiran Statistik) Duration : 3 hours (Masa : 3 jam)